2020
DOI: 10.24071/jpsc.001674
|View full text |Cite
|
Sign up to set email alerts
|

THE SUB-CHRONIC TOXICITY TEST OF MENIRAN (Phyllanthus niruri L.) AND PEGAGAN (Centella asiatica) EXTRACT IN WISTAR STRAIN RATS ON LIVER AND KIDNEY FUNCTION

Abstract: Meniran (Phyllantus niruri L.) and Pegagan (Centella asiatica L.) was proven had activity that considered as an antioxidant. However, the safety was not confirmed. This research is intended to evaluate sub-chronic toxicity of standardized combination extract of meniran and pegagan on liver and kidney function. This research used post-test-control design. Twenty female and twenty male Wistar strain rats divided into 4 groups. The first group was controlled in dosage of CMC Na 0.5%. The others were given a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The previous study revealed that the Indian almond plant was used as a medicinal for fever, itching, and wound healing (Nugroho et al, 2019b;Nugroho et al, 2017;Nugroho et al, 2016;Nugroho et al, 2019c). Toxicity test is a test to evaluate the safety aspects of a drug intended as a medicinal product (Makalalag et al, 2019;Mangirang et al, 2019;Wresdiyati & Handharyani, 2019), While the subchronic toxicity test is a test to evaluate the toxicity of a compound that is performed for a long duration time (Darmawan et al, 2020;Kasmawati et al, 2020). Further, subchronic toxicity test needs to be done on the Indian almond leaves, to evaluate the toxic effects on liver histology.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study revealed that the Indian almond plant was used as a medicinal for fever, itching, and wound healing (Nugroho et al, 2019b;Nugroho et al, 2017;Nugroho et al, 2016;Nugroho et al, 2019c). Toxicity test is a test to evaluate the safety aspects of a drug intended as a medicinal product (Makalalag et al, 2019;Mangirang et al, 2019;Wresdiyati & Handharyani, 2019), While the subchronic toxicity test is a test to evaluate the toxicity of a compound that is performed for a long duration time (Darmawan et al, 2020;Kasmawati et al, 2020). Further, subchronic toxicity test needs to be done on the Indian almond leaves, to evaluate the toxic effects on liver histology.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study revealed that the almond plant was used as a medicinal for fever, itching, and wound healing (Nugroho et al, 2019b;Nugroho et al, 2017;Nugroho et al, 2016;Nugroho et al, 2019c). Toxicity test is a test to evaluate the safety aspects of a drug intended as a medicinal product (Makalalag et al, 2019;Mangirang et al, 2019;Wresdiyati & Handharyani, 2019), While the subchronic toxicity test is a test to evaluate the toxicity of a compound that is performed for a long duration time (Darmawan et al, 2020;Kasmawati et al, 2020). Further, subchronic toxicity test needs to be done on the Indian almond leaves, to evaluate the toxic effects on liver histology.…”
Section: Introductionmentioning
confidence: 99%